Penerapan Kompetensi Tutor dalam Meningkatkan Motivasi Belajar Peserta Didik Paket B SKB Gudo Jombang - Laila, Siti Nur; Mardliyah, Sjafiatul (J+PLUS UNESA, 2023)
This study aims to examine and analyze the application of tutor competence in increasing the learning motivation of Package B students at SKB Gudo Jombang. This study uses qualitative research with a qualitative descriptive research type. There were 9 informants in this study, including student tutors, tutors and students. The techniques used are interviews, observation and documentation. The results of this study indicate that 80% of SKB Gudo Jombang's package B tutors have taken steps to be able to improve their competence and to support it all one of the ways to do this is to improve their quality and self-esteem by looking for references such as attending workshops organized by SKB, internet sources and many others that can improve the quality of competence of an educator. Tutors and tutors for package B students at SKB Gudo Jombang have good communication with students, fellow educators, and the surrounding community, but tutors don't really socialize with the guardians of their students, because according to students, their parents rarely meet with tutors. in the SKB. The learning motivation of the Gudo Jombang SKB package B students is quite good. This can be seen from the enthusiasm and enthusiasm in participating in the learning that has been conveyed by tutors and tutors of package B students at SKB Gudo Jombang. Of course this is very good and extraordinary progress because the goal of tutor competence has been achieved.